Compound Preposition of Minangkabau Language - Mac Aditiawarman (Fakultas Sastra Universitas Ekasakti, 2018)
Some Minangkabau prepositions have high ability of combining with each other, they are: (a) bak ‘like’, (b) cando ‘like’, (c) dari ‘from’, (d) daripado ‘than’, (e) dek ‘ because, at, by, (f) di ‘at’ (g) jo‘with’, (h) kacuali ‘except’, and (i) kapado ‘to’ (j) sampai ‘until’. There are 2 categories of compound prepositions. Fisrt, some of the compound prepositions are the combination of two prepositions that have same meaning (synonym). One of the compound synonym prepositions can be deleted in their structure environment by using ellipsis technique and the deletion does not disturb the compound meaning. Second, the combination of two or more than two prepositions that have different meaning. Ellipsis cannot be applied to these compound prepositions.